The investigation of Cushing syndrome: essentials in optimizing appropriate diagnosis and management. - Juszczak, A; Grossman, A (2012)
The investigation of Cushing syndrome (CS) should start with careful history taking and clinical examination, and exogenous steroid usage must be excluded. It is essential to confirm hypercortisolism before further investigations are undertaken. The recommended first-line tests include midnight salivary cortisol and/or the 1 mg overnight or low-dose dexamethasone suppression tests. The next step is to differentiate adrenocorticotrophin (ACTH)-dependent from ACTH-independent CS by measuring ACTH. With ACTH-dependence, further investigations should differentiate pituitary-dependent from ectopic ACTH-dependent CS. Many dynamic tests may be considered, but we suggest that bilateral inferior petrosal sinus sampling should be performed in almost all patients with ACTH-dependent CS, except for patients with a pituitary macroadenoma. Imaging should include MR scanning of the pituitary, and CT scanning of the chest and abdomen to look for an ectopic source. Confirmation of the diagnosis of CS and accurate localization of its source are vital to optimize therapy for this complex disorder.